Fermentative processes for the upcycling of xylose to xylitol by immobilized cells of Pichia fermentans WC1507 - Ranieri, Raffaella; Candeliere, Francesco; Moreno-García, Jaime; Mauricio, Juan Carlos; Rossi, Maddalena; Raimondi, Stefano; Amaretti, Alberto (Frontiers in Bioengineering and Biotechnology, 2024)
Xylitol is a pentose-polyol widely applied in the food and pharmaceutical industry. It can be produced from lignocellulosic biomass, valorizing second-generation feedstocks. Biotechnological production of xylitol requires scalable solutions suitable for industrial scale processes. Immobilized-cells systems offer numerous advantages. Although fungal pellet carriers have gained attention, their application in xylitol production remains unexplored.In this study, the yeast strain Pichia fermentans WC 1507 was employed for xylitol production. The optimal conditions were observed with free-cell cultures at pH above 3.5, low oxygenation, and medium containing (NH4)2SO4 and yeast extract as nitrogen sources (xylitol titer 79.4 g/L, YP/S 66.3%, and volumetric productivity 1.3 g/L/h). Yeast cells were immobilized using inactive Aspergillus oryzae pellet mycelial carrier (MC) and alginate beads (AB) and were tested in flasks over three consecutive production runs. Additionally, the effect of a 0.2% w/v alginate layer, coating the outer surface of the carriers (cMC and cAB, respectively), was examined. While YP/S values observed with both immobilized and free cells were similar, the immobilized cells exhibited lower final xylitol titer and volumetric productivity, likely due to mass transfer limitations. AB and cAB outperformed MC and cMC.The uncoated AB carriers were tested in a laboratory-scale airlift bioreactor, which demonstrated a progressive increase in xylitol production in a repeated batch process: in the third run, a xylitol titer of 63.0 g/L, YP/S of 61.5%, and volumetric productivity of 0.52 g/L/h were achieved.This study confirmed P. fermentans WC 1507 as a promising strain for xylitol production in both freeand entrapped-cells systems. Considering the performance of the wild strain, a metabolic engineering intervention aiming at further improving the efficiency of xylitol production could be justified. MC and AB proved to be viable supports for cell immobilization, but additional process development is necessary to identify the optimal bioreactor configuration and fermentation conditions.